Fecal microbiota transplantation from Helicobacter pylori carriers following bismuth quadruple therapy exacerbates alcohol-related liver disease in mice via LPS-induced activation of hepatic TLR4/NF-κB/NLRP3 signaling - Huihui Gao; Hangming Bai; Yanyan Su; Yuting Gao; Hui Fang; Donghang Li; Youren Yu; Xing Lu; Dasheng Xia; Daqing Mao; Yi Luo (Journal of Translational Medicine)
Abstract Background Helicobacter pylori infection is common in patients with alcohol-related liver disease (ALD), and bismuth quadruple therapy (BQT) is widely used for eradication. However, its impact on ALD remains unclear. This study aims to characterize BQT-induced gut microbiota alterations in asymptomatic H. pylori carriers and evaluate their effect on an ALD mouse model. Methods Metagenomic sequencing was conducted to assess the gut microbiota composition of individuals before and after BQT. Fecal microbiota transplantation (FMT) from these donors was performed in an ALD mouse model. Gut microbiota in mice was analyzed by 16S rRNA sequencing. Liver and intestinal parameters were assessed using western blot, RT-qPCR, histopathology, ELISA, and flow cytometry. Results BQT treatment significantly altered the gut microbiota in H. pylori carriers, increasing the abundance of opportunistic pathogens, including Klebsiella pneumoniae, Escherichia coli, Klebsiella quasipneumoniae, and Klebsiella variicola, while decreasing beneficial bacteria such as Bifidobacterium, Eubacterium, Bacteroides, Faecalibacterium, and Blautia. In ALD mice receiving FMT from post-BQT donors, exacerbated gut dysbiosis was observed, marked by an enrichment of Enterobacteriaceae and Escherichia-Shigella. These microbiota changes were associated with impairment of intestinal barrier integrity, as evidenced by reduced levels of mucins, tight junction proteins, and antimicrobial peptides, along with a decrease in Treg cells and an increase in Th17 and Th1 cells. Additionally, this dysbiosis led to elevated serum lipopolysaccharide (LPS) levels, which activated the hepatic NLRP3 inflammasome pathway and subsequently increased IL-18 and IL-1β levels. Furthermore, liver function and oxidative stress markers, including ALT, AST, MDA, GSSG/GSH ratio, and SOD, were significantly elevated, indicating severe liver dysfunction and increased oxidative stress. Finally, probiotic supplementation effectively mitigated the negative effects of BQT-induced gut microbiota remodeling on ALD in mice. Conclusions BQT markedly alters the gut microbiota in H. pylori carriers, promoting dysbiosis that exacerbates ALD in mice via LPS-mediated activation of hepatic inflammatory pathways. These findings highlight the need for careful consideration of BQT use in ALD patients.